2016
DOI: 10.1021/acs.jpcc.6b00304
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Experiments and Calculations on the Polymorphisms of 2,4,6,8,10,12-Hexanitro-2,4,6,8,10,12-hexaazaisowurtzitane (CL-20) Precipitated by Solvent/Antisolvent Method

Abstract: 2,4,6,8,10,12-Hexanitro-2,4,6,8,10,12-hexaazaisowurtzitane (CL-20) is the most powerful explosive. However, the application of this compound is limited by its high sensitivity and serious polymorphic transformations. Thus, elucidating the mechanism of crystallization and polymorphic transformation of CL-20 is crucial. This work presents a comparative study of experiments and calculations to clarify the mechanism of CL-20 precipitation using an solvent/antisolvent method. Calculations show that the β-formed CL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 44 publications
(95 reference statements)
2
41
0
Order By: Relevance
“…The design and preparation of high-energy density materials (HEDMs) with desired properties is one of the hotspots in the research of energetic materials. , Many experimental and theoretical studies have been devoted to improving the performance of energetic materials by exploring a variety of new strategies. However, it remains a challenge to design and construct energetic crystals with the highest possible energy density and the maximum possible chemical stability owing to the contradictory relationship between power and safety.…”
Section: Introductionmentioning
confidence: 99%
“…The design and preparation of high-energy density materials (HEDMs) with desired properties is one of the hotspots in the research of energetic materials. , Many experimental and theoretical studies have been devoted to improving the performance of energetic materials by exploring a variety of new strategies. However, it remains a challenge to design and construct energetic crystals with the highest possible energy density and the maximum possible chemical stability owing to the contradictory relationship between power and safety.…”
Section: Introductionmentioning
confidence: 99%
“…33 Calculation results showed that solvents lowered the energy barrier (ΔE) of the phase transformation, and the solvents with the higher polarity, especially water, more significantly decreased ΔE. 34 A similar effect might exist in the system of HMX with highpolarity water molecules because water molecules strongly interacted even with neutral β-HMX through negatively charged NO 2 groups. 35 This interaction could sufficiently lower the ΔE and permit the equilibrium within a shorter period (e.g., several hours).…”
Section: ■ Results and Discussionmentioning
confidence: 91%
“…Thermodynamic properties are crucial to energetic crystals. For example, COMPASS-MD simulations were used to compare the total energies for α/γ, β, and ε-formed conformations of CL-20 with or without solvents; as a result, β-CL-20 is the most energetically favored and easily converted into ε-CL-20 crystal [ 85 ]. COMPASS was also employed to calculate lattice energy for a series of co-crystals involving CL-20, HMX, TNT, BTF, TNB, TNA, MATNB, or TNAZ molecules [ 86 ].…”
Section: Consistent Forcefields and Their Applications For Emsmentioning
confidence: 99%